Comparative Study of VIA and PAP Smear As a Screening Tool for Preinvasive and Early Invasive Cervical Cancer - Meena, Naik; Rekha, Ratnani; Anju, Pungle (International Journal of Innovative Research in Medical Science, 2017)
Introduction - Cervical cancer is the 2nd common cancer among women worldwide. It is also the leading cause of cancer related mortality in women globally. Due to lack of effective screening program in developing countries, majority of cervical cancer deaths happen in low resource countries. Well organized screening program by cytology has substantially reduced burden of cervical cancer in developed countries, however in developing countries, pap smear based screening program is not feasible due to lack of infrastructure, trined personnel and labs, and funds. Thus alternate screening methods have been studied. Visual screening methods that are simple, cheap and give instant results have been widely studied. In this study we compared the test performance of VIA and PAP screening Material and methods - This is a cross sectional study conducted at CCM medical college, kachandur, durg, between May 2016 to December 2016 over a period of 6 months in Gynae OPD using the existing infrastructure and manpower. All sexually active women between 21-65 yrs of age coming to gynae OPD with various complaints were screened with VIA /VILI and PAP smear in their first visit. Positive cases underwent biopsy and histopathological study done. The sensitivity, specificity, PPV and NPV of VIA and PAP for detection of CIN and early invasive ca cx was determined and compared. Results - Sensitivity of VIA in our study is 97 % but specificity is 56 %. Positive predictive value of VIA thus is low ie 52.25%. But negative predictive value is very good, about 97 %. Hence VIA test is an ideal screening tool as it is unlikely to miss any lesion esp high grade lesion. But it may over diagnose hence lead to more no of patients referred or subjected to colposcopy and biopsy. For PAP test sensitivity is very low it is coming to 39.5% in our study. But specificity was close to 90 %. One more drawback of PAP is lost to follow up as reports are available after 4-5 days and many patients do not come for follow-up hence many positive e cases might be missed. Comparing both the tests VIA is more sensitive while PAP is more specific. Conclusion - VIA can be used as a screening test for cervical cancer and CIN as it is easy, cheap, quick and simple. It does not require any additional infrastructure or cost to do the test. Hence can be easily implemented in low resource settings at grass root level.